2022
DOI: 10.3389/fmed.2022.791352
|View full text |Cite
|
Sign up to set email alerts
|

Online, Face-to-Face, or Blended Learning? Faculty and Medical Students' Perceptions During the COVID-19 Pandemic: A Mixed-Method Study

Abstract: BackgroundCOVID-19 pandemic forced educational institutions to adopt online methods which were inevitable to keep continuity of education across all academia after suspension of traditional educational systems. The aim of this study was to explore the experience of faculty and students of online and face-to-face learning, and their preference of the mode of learning after the pandemic.MethodsThis is a mixed-method study. Quantitative data was collected through a survey from 194 medical students and 33 faculty … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 63 publications
12
39
0
1
Order By: Relevance
“…This agrees with the findings of Halbert et al, 18 who reported that medical students have chosen to remain on clinical placements, even though they had concerns about their personal safety. Also, this is congruent with a study from the same university by Atwa et al, 6 who reported that both faculty members and medical students were in favor for face-to-face and blended learning compared to online learning in the clinical context.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This agrees with the findings of Halbert et al, 18 who reported that medical students have chosen to remain on clinical placements, even though they had concerns about their personal safety. Also, this is congruent with a study from the same university by Atwa et al, 6 who reported that both faculty members and medical students were in favor for face-to-face and blended learning compared to online learning in the clinical context.…”
Section: Discussionsupporting
confidence: 88%
“…Armstrong-Mensah et al 22 found that students were still motivated to learn and to complete their assessments and assignments on time in distance online learning during the COVID-19 pandemic. Also, Atwa et al 6 reported in their study that most of the students felt actively engaged in online lessons during the pandemic and they could also collaborate with other students, which was also found in this study. As well, Kumar et al, 23 found that interactivity among students during online sessions could be maintained, as reported by most of the teachers in their study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations